2016
DOI: 10.1177/0907568216643146
|View full text |Cite
|
Sign up to set email alerts
|

Participation or pedagogy? Ambiguities and tensions surrounding the facilitation of children as researchers

Abstract: Ambiguities and tensions can arise when children are facilitated to act as 'primary researchers' concerning whether this is primarily to support their 'participation' in knowledge production and, with the knowledge produced, in relevant decision-making processes or whether it is mainly for any educational benefits. This paper considers these ambiguities and tensions theoretically and by using evidence from a study where English primary school children were supported to conduct their own research projects. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…While CoPI is a pre-determined technique, it is unequivocally open in terms of adopting the 'methodological attitude' (Gallacher and Gallagher 2008, 513, italics in original) that allows for wide-ranging responses. Kim (2017) asks where the emphasis lies in adopting a pedagogical approach and cautions that 'linking children's research directly with inquirybased learning or learner-centred education seems inappropriate, and pursuing it mainly for its pedagogical benefits may obscure what research is fundamentally for' (89; italics in the original). Research is an inquiry -whether initiated by children or adults, together or separately -and philosophical inquiry offers a complementary approach.…”
Section: Resultsmentioning
confidence: 99%
“…While CoPI is a pre-determined technique, it is unequivocally open in terms of adopting the 'methodological attitude' (Gallacher and Gallagher 2008, 513, italics in original) that allows for wide-ranging responses. Kim (2017) asks where the emphasis lies in adopting a pedagogical approach and cautions that 'linking children's research directly with inquirybased learning or learner-centred education seems inappropriate, and pursuing it mainly for its pedagogical benefits may obscure what research is fundamentally for' (89; italics in the original). Research is an inquiry -whether initiated by children or adults, together or separately -and philosophical inquiry offers a complementary approach.…”
Section: Resultsmentioning
confidence: 99%
“…Other research relationships were also discussed in the literature, particularly in papers reporting on work carried out in schools, where competing agendas and practices may be at play. In Kim's work (Kim 2017), for example, the head teacher tried to steer the children towards certain topics and, while this was not ideal, she found it difficult to intervene as the head teacher was also the main gatekeeper to the children. Cox and Robinson-Pant (2008) described teachers' concern with 'anarchy' and the belief that their educational, legal and moral commitments and duties of care obliged them to take 'ultimate responsibility for decisions' (p. 461), thus limiting the children's input.…”
Section: Theme 2: Power and Research Relationshipsmentioning
confidence: 99%
“…Many of the empirical studies identified through the review included an element of training. Some described particular training programmes undertaken as part of a particular project (Kellett 2010;Kim 2017;Taylor et al 2014) others focused on training for particular parts of a research project, e.g., concept/theme development (Dunn 2015) or data analysis (Coad and Evans 2007). In addition, it was agreed that children needed to be taught about and have a basic understanding of confidentiality and ethics (Coad and Evans 2007).…”
Section: Theme 4: Competence and Skillsmentioning
confidence: 99%
“…The youth leader keenly supported this suggestion as there was a surplus to the spending budget seeing this potential outing as a social event having an educational benefit rather than a research methodology. Kim (2017) suggests that often blurred boundaries exist between research promoted for educational benefits rather than for supporting the participation of young people in knowledge production. While acknowledging the ambiguities and tensions surrounding the facilitation of young people in research design, it was felt that responding positively to the young people’s suggestion would enable them to take ownership of parts of the research.…”
Section: Background To the Case Studymentioning
confidence: 99%